A Review of Research Opportunities in Fog and IoT (International Journal of Innovative Research in Computer Science & Technology, 2021)
Within cloud-to-things gamut, Fog is an  embryonic design for storing data, performing computations,  controlling applications that allocates many of such facilities to the end users. It is applicable to both wireline and mobile  situations, spans software as well as hardware, sits on the  edge of network as well as among end users and across  access networks, and encompasses control as well as data  planes. The review spots most noteworthy applications of fog  computing. It supports an increasing number of applications  as an architecture that includes fifth-generation (5G) wireless  systems, Internet of Things (IoT), and integrated artificial  intelligence (AI). The possibilities and problems of fog are  summarized in this survey study, which focuses mainly on  the networking environment of IoT. Fog is importance edge's  stems from the conventional cloud's inadequacies as well as  the development of new possibilities for the IoT, 5G, and  embedded AI.
Keywords: Edge computing; Edge networking; Fog computing; Fog networking; Internet of Things (IoT)